Profil Kemampuan Berpikir Kritis Siswa Kelas VII SMP Negeri 8 Jember Dalam Menyelesaikan Soal Segi Empat Berstandar AKM - Dzulfiqar Fikri Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
A capability profile represents an individual’s natural depiction in accomplishing tasks by utilizing their abilities. One of the essential cognitive skills required by students is critical thinking skills. Critical thinking skill is employed by students to solve mathematical problems. This study intends to describe the critical thinking ability profiles of seventh-grade students at SMP Negeri 8 Jember in solving AKM-standardized quadrilateral problems. The research method used is a descriptive method with a qualitative approach. This type of research is expected to provide a detailed depiction of students’ critical thinking ability profiles in addressing AKM-standardized quadrilateral tasks. Data were collected using two techniques: testing and interviews. Three students with high, medium, and low critical thinking skills were selected based on the results of the test to proceed to the interview. Data analysis consisted of three stages: instrument validity analysis, critical thinking ability test analysis, and analysis of interview results. The findings indicate that students with high critical thinking ability were able to obtain scores equal to or greater than 30, according to the scoring criteria, and demonstrated excellent performance across all critical thinking indicators in the given problems. Students with moderate critical thinking ability were able to meet only some of the critical thinking indicators and achieved scores ranging from 20 to less than 30. In contrast, students with low critical thinking ability met only one critical thinking indicator and obtained scores below 20, based on the scoring criteria..
Reaploud Repository Hasyim April 2026
Keywords: Student Ability Profile; Critical Thinking; Minimum Competency Assessment